Air pollution particles and iron homeostasis - Ghio, Andrew J.; Soukup, Joleen M.; Dailey, Lisa A. (Biochimica et biophysica acta, 2016)
The mechanism underlying biological effects, including pro-inflammatory outcomes, of particles deposited in the lung has not been defined. A disruption in iron homeostasis follows exposure of cells to all particulate matter including air pollution particles. Following endocytosis, functional groups at the surface of retained particle complex iron available in the cell. In response to a reduction in concentrations of requisite iron, a functional deficiency can result intracellularly. Superoxide production by the cell exposed to a particle increases ferrireduction which facilitates import of iron with the objective being the reversal of the metal deficiency. Failure to resolve the functional iron deficiency following cell exposure to particles activates kinases and transcription factors resulting in a release of inflammatory mediators and inflammation. Tissue injury is the end product of this disruption in iron homeostasis initiated by the particle exposure. Elevation of available iron to the cell precludes deficiency of the metal and either diminishes or eliminates biological effects. Recognition of the pathway for biological effects after particle exposure to involve a functional deficiency of iron suggests novel therapies such as metal supplementation (e.g. inhaled and oral). In addition, the demonstration of a shared mechanism of biological effects allows understanding the common clinical, physiological, and pathological presentation following exposure to disparate particles. This article is part of a Special Issue entitled Air Pollution, edited by Wenjun Ding, Andrew J. Ghio and Weidong Wu. •A disruption in iron homeostasis is proposed as the pathway common to the biological effects of all particulate matter•Oxidative stress, kinase and transcription factor activation, and mediator release after particles result from a functional iron deficiency•Recognition of this pathway suggests novel therapies after particle exposure such as metal supplementation